Braving the Storm: Suicide in Clay County, 1893 – 1905 - Conner, William (Kansas State University, The Chapman Center for Rural Studies, 2010)
The author creates a vivid picture of turn of the century rural life as often impoverished, harsh, and filled with economic loss. He examines the unusually high suicide rate among young farmers who lost their land in the Panic of 1893. This study uses Clay County coroner and funeral home records.
William Conner, “Braving the Storm: Suicide in Clay County, 1893 – 1905,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/217.
Keywords: Clay County; Kansas Pacific Railroad; Panic of 1893; suicide; Coatsworth sisters; Union Pacific Railroad